DAMPAK PEMBELIAN ONLINE TERHADAP OMZET PENJUALAN BUSANA WANITA DI BLOK B LANTAI LG LOS A-D, PASAR TANAH ABANG - Mrs Fadillah; Vega Anismadiyah (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2019)
Market digitalization provides a great opportunity for businesses. However, the negative impact of the online market has caused thousands of businessmen to go bankrupt. The situation, must be addressed by enthusiasm, so that the impact on business progress. This study aims to examine the effect of online purchases on sales growth. The object of research is Tanah Abang Market, block B with a sample of 50 fashion entrepreneurs. The research method uses quantitative with linear regression analysis. The results showed, there is a large potential for online purchases on sales growth. In fact, it is predicted to be able to eliminate restrictions, if business people concentrate on improving services and affordable prices. In addition, it is possible to form a diverse market segmentation. However, market characteristics are more sensitive to discomfort or loss